Photon energy reconstruction with the MEG II liquid xenon calorimeter - Yamamoto Kensuke; Ban Sei; Gerritzen Lukas; Iwamoto Toshiyuki; Koboyashi Satoru; Matsushita Ayaka; Mori Toshinori; Onda Rina; Ootani Wataru; Oya Atsushi (EPJ Web of Conferences)
The MEG II experiment searches for a charged-lepton-flavour-violating μ → eε with the target sensitivity of 6×10−14. A liquid xenon calorimeter with VUV-sensitive photosensors measures photon position, timing, and energy. This paper concentrates on the precise photon energy reconstruction with the MEG II liquid xenon calorimeter. Since a muon beam rate is 3–5 × 107 s−1, multi-photon elimination analysis is performed using waveform analysis techniques such as a template waveform fit. As a result, background events in the energy range of 48–58 MeV were reduced by 34 %. The calibration of the energy scale of the calorimeter with several calibration sources is also discussed to achieve a high resolution of 1 .8 %.